2017
DOI: 10.1007/s10886-017-0849-5
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Community-Level Effects of Genetic Variation in Foliar Wax Chemistry in the Forest Tree Eucalyptus globulus

Abstract: Genetic variation in foundation trees can influence dependent communities, but little is known about the mechanisms driving these extended genetic effects. We studied the potential chemical drivers of genetic variation in the dependent foliar community of the focal tree Eucalyptus globulus. We focus on the role of cuticular waxes and compare the effects to that of the terpenes, a well-studied group of secondary compounds known to be bioactive in eucalypts. The canopy community was quantified based on the abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Studies in poplar trees have shown that intra-specific genotypic variation has strong effects on the concentration of compounds in the two major groups of phenolic defences, condensed tannins and salicinoids (e.g., Donaldson and Lindroth 2007). Genotypic effects on tree phytochemistry were, e.g., also shown in studies on willow (Barbour et al 2015), Eucalyptus (Barbour et al 2009; Gosney et al 2017) and birch (Haviola et al 2012). The phytochemistry of trees has been suggested to be the intermediate link between tree genes and the arthropods associated with trees by the genetic similarity rule (Bangert et al 2006).…”
Section: The Tree Genotype Determines Intra-specific Variation In Phymentioning
confidence: 58%
“…Studies in poplar trees have shown that intra-specific genotypic variation has strong effects on the concentration of compounds in the two major groups of phenolic defences, condensed tannins and salicinoids (e.g., Donaldson and Lindroth 2007). Genotypic effects on tree phytochemistry were, e.g., also shown in studies on willow (Barbour et al 2015), Eucalyptus (Barbour et al 2009; Gosney et al 2017) and birch (Haviola et al 2012). The phytochemistry of trees has been suggested to be the intermediate link between tree genes and the arthropods associated with trees by the genetic similarity rule (Bangert et al 2006).…”
Section: The Tree Genotype Determines Intra-specific Variation In Phymentioning
confidence: 58%
“…However, there are largely unappreciated extended effects of provenance choice on organisms that colonize and inhabit restoration plantings (Whitham et al 2006, Crémieux et al 2008, Bucharova 2017). Provenance effects have been shown to affect individual organism responses, as well as biotic communities both above- (Bucharova et al 2016, Gosney et al 2017) and belowground (Senior et al 2016, Gehring et al 2017, Urbina et al 2018. The coevolutionary relationships between local provenances and their dependent communities (e.g., Toju andSota 2005, Gehring et al 2017) further emphasize the importance of considering the extended effects of using local or nonlocal provenances on ecological networks.…”
Section: Research Prioritiesmentioning
confidence: 99%
“…Phenylethyl heptanoate has been identified in another species of rose, Rosa rugosa , 38 and also in citrus, Stachys species and vanillin 39‐41 . Phenylethyl arachidate and phenylethyl behenate have been found in potato, poplar and eucalyptus, phenylethyl behenate was also found in Sambucus nigra 42‐46 . Phenylethyl heneicosanoate has also been descripted in eucalyptus 45 .…”
Section: Resultsmentioning
confidence: 96%
“…[39][40][41] Phenylethyl arachidate and phenylethyl behenate have been found in potato, poplar and eucalyptus, phenylethyl behenate was also found in Sambucus nigra. [42][43][44][45][46] Phenylethyl heneicosanoate has also been descripted in eucalyptus. 45 Phenylethyl linolenate has been identified in jasmine absolute and karo-karounde absolute.…”
Section: Standardmentioning
confidence: 99%